Essential contact lens practice 13: The future of contact lenses. Issue 6 (June 2021) - Hiscox, Rachel; Nagra, Manbir
Abstract : In the final article in our major series about modern contact lens practice edited by Dr Rachel Hiscox, Dr Manbir Nagra takes a look at some of the exciting developments in contact lens practice likely to impact on eye care in the future.